Muir–Torre syndrome: a case of unusual coexisting genetic mutations. (1st March 2022) - Cino, D.; Drumm, C.; Sheahan, K.; D'Arcy, C.; Nolan, N.; Hoti, E.; Winter, D.; O'Duffy, F.; Dolan, R.; Moriarty, B.
Abstract: Patients with Muir–Torre syndrome (MTS) commonly have germline mismatch repair mutations in MLH1, MSH2 or MSH6, with a strong predominance in MSH2. A subset of approximately one‐third of patients will instead have an autosomal recessive base excision repair mutation in MUTYH called MUTYH polyposis. To the best of our knowledge, this is the first report of coexisting germline MSH2 and MUTYH mutations in a patient with MTS.